ChemInform Abstract: Divergent Synthesis of Pseudoenantiomers for ABC‐Ring Moiety of Steroids. Issue 38 (10th September 2014) - Furuta, Miyu; Hanaya, Kengo; Sugai, Takeshi; Shoji, Mitsuru
Abstract One of the key steps in the synthesis of the ABC‐Ring moiety is the radical domino cyclization reaction of the precursor (I).